AL-HAMZAH WA ASHWAT AL-ILLAH BAINA AL-WASHFI AL-NUTHQI WA AL-BINYAH AL-MAQTHAIYYAH - Dziyab, Musthafa Bani; al-Dakeel, Muhammad Majid; Syahadaat, Majdi Husain Ahmad (Laboratorium Informasi & Publikasi Fakultas Humaniora UIN Maulana Malik Ibrahim Malang, 2016)
This study investigates the relation between the hamza and vowel sounds as it offers the phonetics' characteristics for both hamza and vowel sounds in their separatedly contexts and for the effect of phonetics' contexts on their phonetics' characteristics. This study concludes that there is a symmetrical relation between the characteristics of the hamza and vowel sounds specially when the vowel sounds come after (a) at the end of the word. In addition to what had been mentioned, this study elaborates the effect of syllabic structure in Arabic on the phonetics' sequences for the vowel sounds which lead to the convert of (w) and (y) to hamza after (a). This conversion is discussed despite the difficulties of the articulations of the sounds.